Peran Permainan Edukatif Dalam Proses Katekese Digital Anak-Anak Usia Dini - Yuni Setiani Merlianta Girsang; Emmeria Tarihoran (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
In this rapid development of technology, digital catechesis for early childhood takes a role in the process of faith education for them. In providing education and teaching to children, new methods are needed that provide new innovations, especially in the catechesis process. Educational games play their role in educating the faith of early childhood children by utilizing platforms available in digital development, namely Quizizz and Kahoot which can be a means for parents and catechists to educate children's faith by utilizing technology so that faith education provided to children gains new innovations.